KARAKTERISTIK PENDERITA HEPATITIS B RAWAT INAP DI RUMAH SAKIT TINGKAT II PUTRI HIJAU KESDAM I/BUKIT BARISAN MEDAN TAHUN 2010-2013 - SRI REZEKI HASANAH; Sori Muda Sarumpaet; Rasmaliah . (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2014)
Hepatitis B is a problem of global public health.WHO,2011 said that HBV had infected more than 350 thousand people in the world and there were 600.000 people had died caused by Hepatitis B acute or cronic. To determine the characteristics of Hepatitis B patients in hospital grade II Putri Hijau Kesdam I/Bukit Barisan Medan 2010-2013, conducted a research with case series design. Population and sample were 108 patients and recorded in hospital medical records. Univariate data were analyzed descriptively while bivariate data were analyzed using Chi-square test, t-test and Anova with 95% CI. Proportion based  on sosiodemographics were groups of age 20-24 years 14,8%,male 78,7%, Islam 85,2%, self employed 34,3%,married 64,8% and living in Medan 83,3%. Level of Bilirubin is not normal 78,7%, type Acute Hepatitis B 78,7%, level of SGOT is high 44,5%, level of SGPT is high 57,4%, average of treatment duration is 10,49 days and returned with outpatient 77,8%. There was no significant difference between sex and level of SGOT (p=0,416), There was no significant different between sex and level of SGPT (p=0,051). There was significant difference between type of Hepatitis B and level of Bilirubin (p=0,019). There was no significant difference between average of treatment duration and condition of returned (p=0,000). They can not be tested using by Chi-square test, age and type of Hepatitis B,age and level of SGOT,age and level of SGPT,also type of Hepatitis B and condition of outpatient. It’s hoped the hospital grade II Putri Hijau Kesdam I/ Bukit Barisan Medan to give advice for Hepatitis B patients acute and chronic to check up serologic and liver function regularly, to complete list of card statue about education, and it’s hoped the next researcher will research about one of  characterictics or some risk factors are more specific. Key words : Hepatitis B, characteristics of patient, hospital grade II Putri Hijau Kesdam I/Bukit Barisan Medan 2010-2013  KARAKTERISTIK PENDERITA HEPATITIS B RAWAT INAP DI RUMAH SAKIT TINGKAT II PUTRI HIJAU KESDAM I/BUKIT BARISAN MEDAN TAHUN 2010-2013